Encounter of an inferior intramolecular cyclization in an approach toward the synthesis of 10-oxo-2-thia[3.2]metacyclophane: Preparation of two isomeric dioxo-2,19-dithia[3.2.3.2]metacyclophanes - Lai, Y.-H. (2014)
Heterocycles